Characteristic Evaluation of Antioxidant Edible Coating Based on Gelatin Broiler Chicken Feet Skin with Addition of Liquid Smoke - Oka, A.; IK. A. Wiyana; M. Hartawan; I N.S. Miwada; S. A. Lindawati (Institute for Research and Community Service, Udayana University, 2017)
The purpose of this study was to evaluate the characteristics of gelatin application from broiler chicken skin as an edible coating that has the potential of antioxidant with liquid smoke. The research method was using Completely Randomized Design (CRD) from gelatin based edible coating from broiler feet skin with smoke concentration treatment each: 0%; 0.5%; 1%; 1.5% and 2%. The results showed that the addition of liquid smoke to a concentration of 2% gave the best results both from the organoleptic aspect (color and aroma) and from the aspect of its antioxidant potential (phenol). Observation of edible microstructure through SEM test on addition of 2% liquid smoke concentration showed edible component composition of edible formula more homogenous than other treatments. The conclusion that the use of liquid smoke as a source of antioxidants has provided an edible alternative to potentially antioxidant characteristics. The concentration of liquid smoke added to this edible preparation of 2% received a positive response of color and taste aspects and contained the highest antioxidant potential.